OPERATION OF ELECTRIC MACHINES CRITERIA FOR SELECTING ELECTRIC MOTORS AND TRANSFORMERS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article provides an overview of the operation of electric machines, the criteria used to select electric motors and transformers, and the importance of proper selection in achieving reliable and efficient system performance.